Convergence of General Theory and Practice in VET : Five theses about the students' motivation for general subjects in VET - Aarkrog, Vibe [Verfasser] (My University, 2008)
"An empirical study of practice related teaching in VET shows that although the teachers relate to practice in both mathematics, physics and chemistry and Danish and English, the students in the technical VET programmes are generally more motivated for learning the former than the latter subjects. It seems easier to establish convergence between theory and practice within mathematics, physics and chemistry than within Danish and English. By formulating five theses about learning and transferring mathematics, physics and chemistry, on the one hand and Danish and English on the other, the purpose of the article is to point to ways of supporting the convergence of general theory and vocational practice." (Autorenreferat, BIBB-Doku)
Keywords: L 1.6 Allgemeinbildende Fächer; L 2 Lehr-Lerngestaltung; Unterricht; Unterrichtsfach; Naturwissenschaftliche Bildung; Sprachunterricht; Lernmotivation; Praxisbezug